Differences in Baby Attachment Behavior to Parents Between Exclusively Breastfed and Non-Exclusive Breastfeeding (Study on Infants Age 6 Months – 3 Years in Candi District, Sidoarjo Regency) - Qurrotul A’yun; Inayah Inayah (Psikologia : Jurnal Psikologi, 2011)
Breast milk (ASI) is the most perfect food for babies. Breastfeeding means providing nutrients with high nutritional value needed for growth and development of the nerves and brain, as well as creating an emotional bond between mother and baby. Learning theory says that the attachment between mother and child begins when the mother breastfeeds the baby as a process of reducing hunger which is the basic drive. The milk given by the mother becomes the primary reinforcer and the mother becomes the secondary reinforcer. (Gewirtz in Hetherington and Parke, 1999 in Ervika 2000, http://usu.co.id Library). The purpose of this study was to determine the differences in the attachment behavior of infants to their parents between those who were exclusively breastfed and those who were not exclusively breastfed. From the results of the t-test the probability is <0.05, which is 0.000, which means that the hypothesis is accepted. Based on the t-test table, t-table at the 95% confidence level, the t-table value is 1.645. Because tcount > ttable, which is 13.832, the hypothesis is accepted. Thus, based on the above test, there are differences in the attachment behavior of babies to their parents between those who are exclusively breastfed and those who are not exclusively breastfed.